Orthodox Perspectives of Theological Dialogue and Christian Unity according to Nikolai Glubokovsky (Forum Theologicum Sardicense, 2025)
Kostadin Nushev, Orthodox Perspectives of Theological Dialogue andChristian Unity according to Nikolai GlubokovskyAfter establishing himself in Bulgaria in the early 1920s and beginning his academicand scientific work at the Theological Faculty of Sofia University, ProfessorGlubokovsky continued to actively research Orthodox theology and science. Healso participated, along with other prominent Russian church clergy and theologians,in numerous international scientific and religious forums. Some of theseforums were dedicated to Christian theological dialogue and various issues relatedto the relationships between the Orthodox Church and Western Christiandenominations. During this period, Professor Glubokovsky participated moreactively, consciously, and confidently in international initiatives and conferencesfocused on theological dialogue with the Anglican and Old Catholic Churches.He attended these forums both as a representative of the Bulgarian theologicaland academic community and as an official delegate of the Bulgarian OrthodoxChurch, as well as a representative of the Russian Orthodox Church and theRussian academic community in Europe. The main purpose of this publicationis to provide a brief commentary on some of the theological arguments presentedby Professor Glubokovsky during these dialogues in 1925 in London. Histheological presentations were published under the broad title “Christian Unityand Enlightenment in the Orthodox Theological Perspective.” The publicationincludes two separate lectures delivered by Professor Glubokovsky in English,respectively at London University and King’s College, London. According toProfessor Glubokovsky, the issues of Christian unity, or „ecumenical unity,“ areamong the most important of the time. These issues should be considered inlight of Biblical and Patristic truths, which are universally important to Orthodoxyand considered “generally accepted axioms” by the higher church hierarchy,theologians, and ordinary Christians.